Valuing and Financing Early Seed Internet Media Company (Case Study: PT ABC) - Rachman, Febryansyah Djatu; Soekarno, Subiakto (Jurnal Aplikasi Manajemen, 2013)
With increasing Internet penetration rate in Indonesia, Indonesia has the potential for being one of the biggest internet user countries. Businesses dwelling on digital marketing and media investment is a new thing in Indonesia. This business has bright prospects and great potential, yet it comes with great uncertainty as well. Thus, only a handful of investors dare to invest in the Internet business world; however, foreign investors with extensive views and insights and considering the future development of Indonesia's economy, do not hesitate to put their money on digital media and advertising business. The internet media business is one of the most competitive yet lucrative industries in the world today. Expected as one of the fastest growing business, internet offers freedom to everybody interested to dive in the business. Considering the prospect of the industry, many entrepreneurs establish a new firm and dive in the business, even oftenwithout adequate resources, therefore they find several hindrances business. A new start-up business is difficult to value, particularly those which focus on high technology and intangible sector. Some of the companies have no revenues, operating losses, even some just don't realize the idea and business plan yet. The reason of the difficulty in valuing new start-up companies is the incomplete financial report or financial statement as well as lack of business activity report. This thesis will cover the financing strategy for a new start-up business, exploring the venture capital funding scheme that supports the development of the company.